Pengaruh Electronic Procurement Terhadap Good Governance Pada Pemerintah Provinsi Bali - adiana, i made budi; Yasa, i Nyoman Mahaendra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
The realization of good governance is a prerequisite for the government in realizing the aspirations of the people and achieving the ideals of the nation and state. One of the government's efforts to make it happen is by procurement of goods / services electronically or electronic procurement. Nevertheless, there are still problems such as the quality of service is not optimal and there is still auction failed with the implementation of e-procurement. This study analyze the influence of electronic procurement on good governance in Bali Provincial Government. This study aims to analyze the direct and indirect influence between Electronic Procurement variables, Employee Commitment, Quality of Procurement Service, and Good Governance in Bali Provincial Government. In this research used descriptive analysis technique and structural equation with SEM alternative PLS. The results of the research shows that the variable of Electronic Procurement and Employee Commitment have positive and significant effect on Quality of Procurement Service with R-Square value of 0,596. In addition, the varibles of Electronic Procurement, Employee Commitment, and Quality of Procurement Service also have a positive and significant effect on Good Governance with R-Square value of 0.723.